Flexible and wake-up free Hf0.5Zr0.5O2 ferroelectric thin films with ultra-low operation voltage and high polarization - Jun-Hui Wang; Tian-Peng Duan; Jia-Jia Liao; Zhi-Peng Wang; Xin-Ran Huang; Shi-Jie Jia; Ke-Yu Bao; Yu-Xin Fan; Bing-Jian Zeng; Li-Mei Jiang; Min Liao; Yi-Chun Zhou; et al. (Journal of Advanced Ceramics)
Flexible and transparent hafnium oxide-based ferroelectric films are attracting widespread attention because of the increasing demand for wearable electronic devices. However, the ultra-low voltage operation with robust and stable ferroelectricity, which is a prerequisite for portable device applications, has not been realized simultaneously. Here, we report flexible Hf0.5Zr0.5O2 ferroelectric films with a saturation voltage of only 1.3/3 V and remanent polarization (2Pr) of 38/60 µC·cm2. Negligible wake-up effect and superior stability resistance to compressive/tensile stress and high temperature up to 150 °C are also demonstrated. The polarization switching dynamics under bending are investigated based on the switching current measurement, suggesting that the intrinsic switching speeds keep almost constant at different bending radii. In addition, there is a negative correlation between the activation field and the compressive or tensile stress, which is due to the lowered energy barrier induced by the in-plane strain applied to the [111]-oriented hexagonal cell. Our work sheds light on the application of flexible, stable, and HfO2-based ferroelectric thin films with ultra-low consumption.